A Review Article of Streptococcus Pyogenes Infection: Rick Factors, Prevention and Management Strategies - Ali, Maryam A.; Kadhim, Shaimaa J; Al-Bayaa, Yasmeen J. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Streptococcus pyogenes is an exclusively human pathogen. This bacterial species is responsible for a large variety of infections.Objective: This review identified published articles on the risk factors, prevention, and control strategies for streptococcus diseases.Methods: A systematic search was carried out to identify papers published on the Web of Science, PubMed, Scopus, and Google Scholar electronic databases in an attempt to provide basic information about Streptococcus infections, potential risks for their spread, and treatment and prevention strategies.Results: The more common methods for Streptococcus pyogenes transmission are through respiratory droplets, and skin lesions brought on by Streptococcus pyogenes contact with infected objects or devices. Another potential mode is foodborne transmission but more research is needed to determine this infection route. Native communities and those of low socio-economic status worldwide were found particularly susceptible to Streptococcus diseases, as well as children, older adults, and those with impaired immune systems. Those groups are susceptible to Streptococcus pyogenes infections and their complications with higher infectious rates in educational institutions, and hospitals, over-crowding, and the continuous increase in social contact. The importance of improving living conditions and personal and hand hygiene is one of the techniques in the management and prevention of Streptococcus pyogenes infections. Infection control methods must be highlighted with greater precision.Conclusion: Prevention and control measures should target the improvement of living conditions, and personal and hand hygiene. Adherence to infection prevention and control practices should be emphasized in high-risk settings.